2013
DOI: 10.1093/hmg/ddt340
|View full text |Cite
|
Sign up to set email alerts
|

The SNM1B/APOLLO DNA nuclease functions in resolution of replication stress and maintenance of common fragile site stability

Abstract: SNM1B/Apollo is a DNA nuclease that has important functions in telomere maintenance and repair of DNA interstrand crosslinks (ICLs) within the Fanconi anemia (FA) pathway. SNM1B is required for efficient localization of key repair proteins, such as the FA protein, FANCD2, to sites of ICL damage and functions epistatically to FANCD2 in cellular survival to ICLs and homology-directed repair. The FA pathway is also activated in response to replication fork stalling. Here, we sought to determine the importance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…DCLRE1B, encoding a 5ʹ-3ʹ exonuclease, has been reported to play a vital role in DNA double-strand break (DSB) repair by affecting efficient localization of BRCA1 and the MRE11/RAD51/NBS1 complex. 76 GATAD2A, encoding a subunit of the nucleosome remodeling and histone deacetylase (NuRD) complex, plays an important role in recruiting NuRD to the sites of damaged chromatin for repair of DSBs by homologous recombination. 35,[77][78][79] Interestingly, we also found that a low expression level of ESR1 was associated with an increase of TMB of cancer-driver genes.…”
Section: Discussionmentioning
confidence: 99%
“…DCLRE1B, encoding a 5ʹ-3ʹ exonuclease, has been reported to play a vital role in DNA double-strand break (DSB) repair by affecting efficient localization of BRCA1 and the MRE11/RAD51/NBS1 complex. 76 GATAD2A, encoding a subunit of the nucleosome remodeling and histone deacetylase (NuRD) complex, plays an important role in recruiting NuRD to the sites of damaged chromatin for repair of DSBs by homologous recombination. 35,[77][78][79] Interestingly, we also found that a low expression level of ESR1 was associated with an increase of TMB of cancer-driver genes.…”
Section: Discussionmentioning
confidence: 99%
“…Required for fork repair and resolving UFBs [ 41 , 50 ] PICH PICH (Plk1 interacting checkpoint) is a helicase/translocase involved in resolving UFBs in mitosis [ 49 ] SNM1B/APOLLO A nuclease component of the FA pathway involved in homology-directed repair. Also facilitates DNA localization of FANCD2 and BRCA1 [ 86 ] Rad51 Component of the HR pathway involved in DSB repair and HJ mediated RF restart [ 47 ] DNA-PKcs NHEJ pathway component [ 47 ] Ligase IV NHEJ pathway component [ 47 ] …”
Section: Maintenance Of Fragile Site Integritymentioning
confidence: 99%
“…Two recent works [ 37 , 38 ] reported that the endonucleases MUS81/EME1 and ERCC1, which contribute to processing a wide variety of DNA structures such as stalled forks and Holliday junctions, are involved in the maintenance of CFSs during mitosis. SNM1B/APOLLO, a nuclease involved in the FANC pathway, also contributes to stabilizing CFSs [ 39 ]. Together, these results strongly suggest that segregation of incompletely replicated chromosomes can still be rescued through accurate processing of non-replicated DNA and that formation of 53BP1 bodies favors faithful repair and/or replication completion in the next cell cycle.…”
Section: Behavior Of Under-replicated Regions At Mitosis and Beyondmentioning
confidence: 99%